Aplicação em sala de aula do experimento Deslocamento no Plano Inclinado para o ensino da função quadrática - Barillari, Paulo Eduardo (Universidade Federal de São Carlos, 2020)
In order to collaborate in overcoming difficulties related to teaching the concept of function and its applications, an interdisciplinary didactic proposal was prepared. The theme was second-degree polynomial function, content linked to the 1st grade of High School. For the construction and validation of the pedagogical product, the basic guidelines proposed by Didactic Engineering were used. An experiment was developed in the area of Physics (Displacement in the Inclined Plane), with different heights corresponding to the elevation of the ramp in relation to the horizontal, of which the model function is quadratic. The students involved were divided into groups to carry out the activities. Each group recorded the experiment and edited the video, enabling the collection of numerical data, composing a table. The analysis started with the data being arranged as points on a Cartesian plane. Observing the pattern of the points found and using algebraic resources, the students obtained the expression of a quadratic function. In another moment, the same data was manipulated with assistance of computational tools. Then, the students solved theoretical problems to deepen and verify the assimilated contents. The application ended with groups meeting in the school's video room to present, socialize and compare the various results obtained. The students were very willing to participate in the proposed activities and were very satisfied with the final products. During the application and development of the works, there was great interactivity between students and teacher, reflecting on a closer and friendly relationship. These activities provided the students with a better understanding of the functions theme, showing that the work achieved the intended purposes.
Classroom application of the experiment Displacement in the Inclined Plane for teaching quadratic function
Keywords: Educação Matemática; Função quadrática; Experimento da física; Modelagem matemática; Engenharia didática; Mathematical education; Quadratic function; Physics experiment; Mathematical modeling; Didactic engineering; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM